Analisis Penerimaan E-Learning sebagai Media Perkuliahan melalui Pendekatan Technology Acceptance Model (TAM) - Ana, Layli; Amin, Hasan (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
Technology Acceptance Model (TAM) is a conceptual framework developed from the Theory of Reasoned Action (TRA) to understand how people accept and use information systems. This model is designed to identify how external factors can influence an individual's beliefs, attitudes, and intentions in using technology. In TAM, there are two key components that are considered to be the main determinants of computer acceptance behavior, namely perceived usefulness (PU) which is the extent to which users believe that the technology can improve their performance, and perceived ease of use (PEOU) which is the level of user belief that the system is easy to operate. This study is a quantitative survey study with 150 active student respondents, data analysis using SEMPLS, the results of the study showed that Perceived Ease of Use (PEU) has a positive effect on Perceived Usefulness (PU) and Attitude Toward Using (ATU), perceived Usefulness (PU) has a positive effect on ATU and Behavioral Intention (BI), Attitude Toward Using (ATU) has a positive effect on Behavioral Intention (BI) and Behavioral Intention (BI) has a positive impact on Actual Use (AU).